The Role Of The Staff In Increasing Guest Satisfaction At The Lake Toba International Cottage Hotel Restaurant - Syahrial Sitorus; Paska Apriani Berutu (Enrichment : Journal of Management, 2021)
In providing services to guests, the implementation of standard operating procedures is very necessary, and the role of a waiter is very supportive in the success of a restaurant, so that guest satisfaction in the waiter service of the Lake Toba International Cottage Hotel. In this study, the authors found the average percentage obtained from the questionnaire, namely about the analysis of the knowledge of the waiter in service, it was found that there were 42% of the waiters who answered always there, 29% of the waiters who answered sometimes and there were 29% of the waiters who answered never in the past. knowledge of service. Then on supervision it was found that there were supervisors who answered always 30%, there were 60% supervisors who answered sometimes and there were 10% supervisor who answered no. Furthermore, regarding guest satisfaction, it was found that there were 74% of guests who were satisfied and 26% of guests felt less satisfied. In writing this final project, the author hopes that all waiters in the restaurant must always pay attention to the appearance and service system that will be provided to guests, so that this can increase comfort and satisfaction to guests, by providing the best service and must know what to expect. the wishes and needs of guests. Waiters are also required to have a way of working that is full of responsibility because waiters are ambassadors of the company which indirectly has to work professionally and more creatively, which is useful for increasing the comfort of guests who come in the service of eating and drinking from guests who come to the restaurant. restaurant